Preservice Teachers’ Use of Web 2.0 Tools and Perspectives on their Use in Real Classroom Environments - İlknur Özpınar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
New understandings and methods have proliferated as technology continues to root itself more deeply in an increasing number of areas within the field of education, causing, naturally, the technology-based tools to find a wider application in assessing students‘ knowledge and progress. With the resulting rapid development of Web applications, Web 2.0 tools have found a niche in a great many steps of the instruction process and have emerged as an integral part of educational technology. Indeed, those studying to become teachers are, quite naturally, one of the most important factors in ensuring that further improvements in this type of technology will be incorporated in mathematics instruction. Accordingly, this study aims to examine what preservice teachers thought of a class during making up part of their teacher training in which they used Web 2.0 tools (e.g., Plickers, Kahoot, Edmodo, ZipGrade) to design activities and lesson plans that they implemented in real classroom settings, which were then discussed in together as a class. The research is conducted with the case study method and the participants consisted of 24 senior preservice teachers of primary school mathematics education in a state university in Turkey. The study‘s data were collected using written interview forms and subsequently analyzed using content analysis. At the end of the study, it was found that Web 2.0 tools contribute to professional development, instruction and student-teacher-parent interaction dimensions for teachers; on the other hand, it was revealed that it contributes to affective characteristics, learning and skills dimensions in terms of students. Concerning limitations, preservice teachers stated that the need for the Internet and technological devices in order to use Web 2.0 tools were significant obstacles to their use. Based on the conclusions, it is recommended that future studies investigate the effects of different Web 2.0 tools on different content areas as part of preservice teacher training.